Low telomerase activity in CD4(+) regulatory T cells in patients with severe chronic GVHD after hematopoietic stem cell transplantation - Kawano, Yutaka (American Society of Hematology, 2011)
CD4(+)CD25(+)Foxp3(+) regulatory T cells (Treg) play an important role in the control of chronic graft-versus-host disease (cGVHD). In this study, we examined telomere length and telomerase activity of Treg and conventional CD4(+) T cells (Tcon) in 61 patients who survived more than 2 years after allogeneic hematopoietic stem cell transplantation. Cell proliferation and expression of Bcl-2 were also measured in each subset. Treg telomere length was shorter and Treg telomerase activity was increased compared with Tcon (P < .0001). After transplantation, Treg were also more highly proliferative than Tcon (P < .0001). Treg number, telomerase activity, and expression of Bcl-2 were each inversely associated with severity of cGVHD. These data indicate that activation of telomerase is not sufficient to prevent telomere shortening in highly proliferative Treg. However, telomerase activation is associated with increased Bcl-2 expression and higher Treg numbers in patients with no or mild cGVHD. In contrast, patients with moderate or severe cGVHD have fewer Treg with lower levels of telomerase activity and Bcl-2 expression. These results suggest that failure to activate Treg telomerase may restrict proliferative capacity and increase apoptotic susceptibility, resulting in the loss of peripheral tolerance and the development of cGVHD.